The democratisation of art CAP as an alternative art space in South Africa - Lochner, Eben (Rhodes University, Faculty of Humanities, Department of Fine Art, 2011)
While formal arts education was inaccessible to many during Apartheid, community-based centres played a significant role in the training of previously disadvantaged artists. By engaging in a socio-political critique of the history of South African art, this thesis argues that even though alternative art spaces are often marginalised, they remain essential to the diversification and democratisation of contemporary South African art today with its re-entry into the international art scene. According to Lize van Robbroeck (2004:52), "some of the fundamental ideals of community arts need to be revised to enrich, democratize and diversify [South Africa's] cultural practice." The aim of my Thesis is to investigate this statement in relation to the contribution the Community Arts Project (CAP) in Cape Town (1977-2003). CAP and other art centres have played an indispensable role in the establishment of black artists and in producing a locally reflective artistic practice in South Africa, even into the 21st century. Through researching the changes the organisation underwent between the 1980s and 1990s, the ways in which such art centres constantly need to respond to the changing sociopolitical landscape around them become clear. Within South Africa these centres were seen to play a significant part in the liberation struggle and then later in nation building. While these centres were well supported by foreign donors in the late 1980s, such funding was withdrawn in 1991 and the majority of art centres collapsed, illustrating to some degree that the training of artist was not valued outside the context of the struggle against apartheid. By interviewing key people and by reading documentation stored at the Manuscripts and Archives department of UCT I have discovered some of the different benefits and hindrances of working in community art centres both during and after Apartheid. This thesis argues that these centres still play a vital role in contributing to the development of South Africa's local art practice and should not be relegated to the sideline.
Keywords: Arts and society -- South Africa; Democracy and the arts -- South Africa; Art -- Political aspects -- South Africa; Apartheid and art -- South Africa